Restoration of cGAS in cancer cells promotes antitumor immunity via transfer of cancer cell–generated cGAMP - Alexander M. Cryer; Pere Dosta; Michelle Z. Dion; Leonardo de la Parra Soto; Eliz Amar-Lewis; Gabriela Garcia de Leon Carmona; Alejandro Abraham Espinosa Pérez; Diego Fernando Ruiz Aguilar; Triana Huerta; Beatriz Nicolás Ruiz; Nathalie Nicole Casteele Hernandez; Yael Soria; et al. (Proceedings of the National Academy of Sciences, 2025)
Cancer cells comprise a significant proportion of the tumor microenvironment (TME) and often have compromised expression or repression of cyclic GMP-AMP (cGAMP) synthase (cGAS), which prevents effective stimulation of interferon genes (STING) signaling. Here, we leverage the cancer cells and hijack their cellular machinery for increased production of cGAMP, differing from conventional strategies whereby synthetic STING agonists are delivered to immune cells in the TME as a bolus dose, are rapidly cleared and can cause systemic toxicity. Increasing evidence suggests that cGAMP derived from cancer cells can act on proximal immune cells, activating STING, contributing to an antitumor immune response. We used lipid nanoparticles (LNPs) to deliver mRNA coding for cGAS which catalyzes the production of cGAMP. We observed dramatic increases in extracellular and intracellular cGAMP when cancer cells were transfected with cGAS mRNA and genomic DNA, the substrate for cGAS. We confirmed that cGAS and cGAMP are functional due to activation of immune cells, through a combination of extracellular transfer and cell–cell contact mechanisms. Treatment of syngeneic murine melanoma with cGAS LNPs reduced tumor growth significantly and further benefit was observed upon combination with immune checkpoint blockade (anti-PD-1). Moreover, we found increased activation in CD8 + T cells, NK cells, macrophages, and dendritic cells in the TME post treatment with cGAS LNPs. These findings highlight how cancer cells can be used to actively contribute to their own elimination and may be a broadly applicable strategy for delivery of other reprogramming molecules to cancer cells and wider therapeutic combinations.